Genome-Wide association analysis of phenotypic traits in Bambara groundnut under drought-stressed and non-stressed conditions based on DArTseq SNP - Odesola, Kafilat Abiodun; Olawuyi, Odunayo Joseph; Paliwal, Rajneesh; Oyatomi, Olaniyi Ajewole; Abberton, Michael T. (Frontiers in Plant Science, 2023)
Abstract Bambara groundnut (BG) (Vigna subterranea[L.] Verdc) is an indigenous, resilient, but underutilized leguminous crop that occurs mostly as genetically heterogeneous landraces with limited information on the drought tolerant attributes. This study elucidates the associations between sequencing-based diversity array technology (DArTseq) and phenotypic character as well as differing indices related to drought tolerance in one hundred accessions of Bambara groundnut. Genome-wide association mapping was conducted on the basis of 5927 DArTs loci with < 20% missing data. The genome wide association study predicted drought tolerance in Bambara accessions for geometric mean productivity (GMP) and stress tolerance index (STI). TVSu-423 had the highest GMP and STI values (28.50, 2.40), while TVSu-2017 had the lowest at GMP (1.74) and STI (0.01) respectively. The relative water content (%) was significantly higher for accessions; TVSu-411 (60.35, 61.49), TVSu-2 (58.29, 53.94), and TVSu-731 (55.17, 58.92) in 2016/2017 and 2017/2018, respectively. The phenotypic characters studied delineated the accessions into two major clusters and five distinct sub-clusters, indicating variations across all the geographical locations. The 5,927 DArTseq genomic markers in association with STI further grouped the 100 accessions into two main clusters. TVSu-1897 from Botswana (Southern Africa) was in the first cluster, while the remaining 99 accessions from Western, Central, and Eastern Africa made up the second cluster. Eight Quantitative Trait Loci (QTLs) were identified using the Bonferroni cut-off points (24346377|F|0-22:A>G-22:A>G, 24384105|F|0-56:A>G-56:A>G, 24385643|F|0-53:G>C-53:G>C, 24385696|F|0-43:A>G-43:A>G, 4177257|F|0-44:A>T-44:A>T, 4182070|F|0-66:G>A-66:G>A, 4183483|F|0-24:G>A-24:G>A, 4183904|F|0-11:C>T-11:C> T) detected under the drought-stressed conditions was discovered to be highly linked with STI. The observation of consistent Single Nucleotide polymorphism (SNPs) in the 2016 and 2017 planting seasons, as well as in combination with the 2016 and 2017 planting seasons, led to the designation of these Quantitative Trait Loci (QTLs) as significant. The drought selected accessions could form basis for hybridization breeding. The identified quantitative trait loci could be useful in marker-assisted selection in drought molecular breeding programs.